Chemically amplified 19F-1H nuclear Overhauser effects. - Kuprov, I; Hore, P (2004)
Chemically induced dynamic nuclear polarisation (CIDNP) is explored as a source of nuclear hyperpolarisation in heteronuclear Overhauser effect experiments. A photochemical reaction proceeding through a radical pair intermediate is used to enhance (19)F nuclear magnetisation in 3-fluorotyrosine by more than an order of magnitude with a corresponding increase in the amplitudes of (19)F-(1)H cross-relaxation and cross-correlation effects. The reactions employed are cyclic and leave the sample chemically unchanged. The potential for enhancing the sensitivity of heteronuclear NOEs in (19)F-labelled proteins is discussed.